Reprentation Struggle Of Arek – Arek Suroboyo In The Film Battle Of Surabaya (Semiotic Analysis Charless Sanders Peirce) - Aziz, Fauzan; Febriana, Poppy (Procedia of Social Sciences and Humanities, 2024)
Film can be a frame for electronic mass communication in an audio-visual media frame that is capable of displaying words, sounds, images and their combinations. Film is also one of the newest forms of communication that has emerged in the world. Films act as a modern means used to spread entertainment which has been a trend in the past, as well as showing stories, events, music, shows, comedy, and other special offerings to the open public. Film also agrees with Prof. such as mental influence and social influence.This research discusses the representation of Arek-Arek Suroboyo from the movie Battle Of Surabaya. The problem in this research is how the struggle contained in the movie. In conducting research, the author uses the research method used by Charless Sanders Peirce which consists of representamen, object, and interpretant. The results of the research using semiotic analysis of Charless Sanders Peirce get denotative meaning, namely the value of struggle. The conclusion of this analysis is to show the struggle of Arek-Arek Suroboyo in the Battle of Surabaya movie. As with the three components of the Charless Sanders Peirce sign, to be specific the representamen depicts the Arek-Arek Suroboyo scene within the Fight Of Surabaya film, the object portrays the Arek-Arek Suroboyo scene, and the interpretant interprets a meaning within the picture and depiction that adjusts the Arek-Arek Suroboyo scene in the Battle Of Surabaya film.